2018
DOI: 10.2147/jpr.s159146
|View full text |Cite
|
Sign up to set email alerts
|

α7 Nicotinic acetylcholine receptor-mediated anti-inflammatory effect in a chronic migraine rat model via the attenuation of glial cell activation

Abstract: BackgroundEvidence suggests that the activation of α7 nicotinic acetylcholine receptor (α7nAChR) can greatly decrease the neuroinflammation response. Neuroinflammation plays a pivotal role in the pathogenesis of chronic migraine (CM). Clinical observations also show that nicotine gum induces analgesic effects in migraine patients. However, whether α7nAChR is involved in CM is unclear.ObjectiveTo investigate the role of α7nAChR in CM and provide a new therapeutic target for CM.Materials and methodsThirty-six ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 73 publications
2
25
0
Order By: Relevance
“…The notion that agonism of microglial α7-nAChR triggers IL-10/β-endorphin pathway is further supported by the facts that the specific inhibitors of MAPK activation attenuated cinobufagin-stimulated IL-10/β-endorphin expression in microglial cells. MAPKs are a family of evolutionally conserved molecules including p38, JNK, and ERK1/2 [75] and have been suggested to be involved in the antiinflammatory properties of α7-nAChRs possibly through modulation of inflammatory cytokine release [23,49,60,69,85]. Our study demonstrated that the specific JNK activation inhibitor SP600125, ERK1/2 activation inhibitor UO126 and p38 activation inhibitor SB203580 significantly blocked the gene expression of IL-10 and POMC in cultured microglia.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The notion that agonism of microglial α7-nAChR triggers IL-10/β-endorphin pathway is further supported by the facts that the specific inhibitors of MAPK activation attenuated cinobufagin-stimulated IL-10/β-endorphin expression in microglial cells. MAPKs are a family of evolutionally conserved molecules including p38, JNK, and ERK1/2 [75] and have been suggested to be involved in the antiinflammatory properties of α7-nAChRs possibly through modulation of inflammatory cytokine release [23,49,60,69,85]. Our study demonstrated that the specific JNK activation inhibitor SP600125, ERK1/2 activation inhibitor UO126 and p38 activation inhibitor SB203580 significantly blocked the gene expression of IL-10 and POMC in cultured microglia.…”
Section: Discussionmentioning
confidence: 49%
“…Activation of mitogen-activated protein kinases (MAPKs), including p38, extracellular signal-related kinases 1/2 (ERK1/2) and c-Jun N-terminal kinases (JNK) [75], was involved in α7-nAChR-induced inhibition of neuroinflammation [23,49,85]. To illustrate which subtype(s) of MAPKs were involved in cinobufagin-induced IL-10/β-endorphin expression, the specific p38 inhibitor SB203580, JNK inhibitor SP600125, and ERK1/2 inhibitor UO126 were used.…”
Section: Activation Of the α7-nachr Mediated Cinobufagininduced Spinamentioning
confidence: 99%
“…Also, activation of α7nAChR by a pre-treatment with a positive allosteric modulator (PAM) reduced LPS-induced expression of the pro-inflammatory markers IL-1β, TNF-α, and the microglial activation marker cluster of differentiation 11b (CD11b) in the hippocampus and prefrontal cortex (PFC) of mice, and even blocked LPS-induced anxiety-like behaviors (Abbas et al, 2017;Alzarea and Rahman, 2019). On the other hand, neuroinflammation induced by the intra-cerebroventricular injection of an inflammatory soup containing prostaglandin E2 (0.2 mM), serotonin (2 mM), bradykinin (2 mM), and histamine (2 mM), in a rat model can also be linked with a decrease in the expression level of α7nAChR in the hippocampus, which can be reversed by the treatment with an α7nAChR agonist (Liu et al, 2018).…”
Section: The Interaction Between Cholinergic Neurons and Glial Cells-mentioning
confidence: 99%
“…It has been confirmed that there might be a bidirectional regulation between α7 nAChR and certain inflammatory factors like interleukin‐1β (IL‐1β) and tumour necrosis factor‐α (TNF‐α) . Moreover, the inflammatory response of PDLSCs could activate multiple signalling pathways, such as those involving glycogen synthase kinase‐3β (GSK‐3β) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that there might be a bidirectional regulation between α7 nAChR and certain inflammatory factors like interleukin-1β (IL-1β) and tumour necrosis factor-α (TNF-α). 16,17 Moreover, the inflammatory response of PDLSCs could activate multiple signalling pathways, such as those involving glycogen synthase kinase-3β (GSK-3β). 18 Furthermore, in the central nervous system, increased expression of phosphorylated GSK-3β can up-regulate the expression and promote the function of α7 nAChR, thus suppressing the progression of degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%